Transplantation of Human Umbilical Cord Blood–Derived Cellular Fraction Improves Left Ventricular Function and Remodeling After Myocardial Ischemia/Reperfusion. Issue 8 (27th September 2019) - Zhao, Lin; Cheng, Guangming; Choksi, Kashyap; Samanta, Anweshan; Girgis, Magdy; Soder, Rupal; Vincent, Robert J.; Wulser, Michael; De Ruyter, Matt; McEnulty, Patrick; Hauptman, Jeryl; Yang, Yanjuan; et al.
Abstract : Rationale: : Human umbilical cord blood (hUCB) contains diverse populations of stem/progenitor cells. Whether hUCB-derived nonhematopoietic cells would induce cardiac repair remains unknown. Objective: : To examine whether intramyocardial transplantation of hUCB-derived CD45 − Lin − nonhematopoietic cellular fraction after a reperfused myocardial infarction in nonimmunosuppressed rats would improve cardiac function and ameliorate ventricular remodeling. Methods and Results: : Nonhematopoietic CD45 − Lin − cells were isolated from hUCB. Flow cytometry and quantitative polymerase chain reaction were used to characterize this subpopulation. Age-matched male Fischer 344 rats underwent a 30-minute coronary occlusion followed by reperfusion and 48 hours later received intramyocardial injection of vehicle or hUCB CD45 − Lin − cells. After 35 days, compared with vehicle-treated rats, CD45 − Lin − cell–treated rats exhibited improved left ventricular function, blunted left ventricular hypertrophy, greater preservation of viable myocardium in the infarct zone, and superior left ventricular remodeling. Mechanistically, hUCB CD45 − Lin − cell injection favorably modulated molecular pathways regulating myocardial fibrosis, cardiomyocyte apoptosis, angiogenesis, and inflammation in postinfarct ventricular myocardium. Rare persistent transplanted human cells could be detected at both 4 and 35 days after myocardial infarction. Conclusions: : Transplantation of hUCB-derived CD45 − Lin − nonhematopoietic cellular subfraction after a reperfused myocardial infarction in nonimmunosuppressed rats ameliorates left ventricular dysfunction and improves remodeling via favorable paracrine modulation of molecular pathways. These findings with human cells in a clinically relevant model of myocardial ischemia/reperfusion in immunocompetent animals may have significant translational implications.Visual Overview: An online visual overview is available for this article. Abstract : Supplemental Digital Content is available in the text.